2020
DOI: 10.1590/s0004-2803.202000000-06
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Synbiotic Supplementation on Gut Functioning and Systemic Inflammation of Community-Dwelling Elders - Secondary Analyses From a Randomized Clinical Trial

Abstract: BACKGROUND: Aging is a complex process marked by alterations on gut functioning and physiology, accompanied by an increase on the inflammatory status, leading to a scenario called “inflammaging”. OBJECTIVE: To evaluate the effects of a synbiotic substance on systemic inflammation, gut functioning of community-dwelling elders. METHODS: This is a secondary analysis from a randomized clinical trial, lasting 24 weeks, including 49 elders, distributed into two groups: SYN (n=25), which received a synbiotic sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
2
0
2
Order By: Relevance
“…It is important to note that PDX has been reported to positively influence stool consistency and bowel function (82). Other studies with B. lactis HN019 TM in combination with other probiotics or prebiotics observed improvements after intervention in bowel functions, such as shortened CTT (26), increased stool frequency and consistency (18,27), reduced flatulence symptoms (21). However, although Botelho et al observed a change in fecal microbiota composition, the study failed to observe a positive effect on bowel function as compared to the placebo group (19) (Table 1).…”
Section: Regulate Gut Motility and Improve Symptoms In Constipationmentioning
confidence: 97%
“…It is important to note that PDX has been reported to positively influence stool consistency and bowel function (82). Other studies with B. lactis HN019 TM in combination with other probiotics or prebiotics observed improvements after intervention in bowel functions, such as shortened CTT (26), increased stool frequency and consistency (18,27), reduced flatulence symptoms (21). However, although Botelho et al observed a change in fecal microbiota composition, the study failed to observe a positive effect on bowel function as compared to the placebo group (19) (Table 1).…”
Section: Regulate Gut Motility and Improve Symptoms In Constipationmentioning
confidence: 97%
“…For example, orally administered Lactobacillus , including Lactobacillus casei , Lactobacillus rhamnosus , Lactobacillus gasseri , Lactobacillus pentosus , Lactobacillus plantarum , Lactobacillus brevis , Lactobacillus johnsonii , Bifidobacterium breve 155 , and Bifidobacterium longum 180 , protected all the mice from influenza-virus-induced pathology and mortality. The main mechanisms include increased antibody production, enhanced natural killer cell activity, and increased IFN-γ and IL-10 by the probiotics 30 . This is consistent with the results obtained from our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Os simbióticos são alimentos ou suplementos incluindo probióticos e prebióticos, o consumo desses ingredientes comprovados com os resultados de alguns estudos mostraram a capacidade de propiciar a estimulação seletiva da microbiota intestinal do hospedeiro e seu funcionamento, diminuindo a atrofia celular e reduzindo a permeabilidade intestinal pelo fortalecimento das junções fechadas e como resultado melhorando o intestino e seu funcionamento e estado inflamatório (Neto et al, 2020).…”
Section: Estudos Indicam Que Os Prebióticos Proporcionam O Aumento De...unclassified